TRADITIONAL DISHES OF BOSNIA AND HERZEGOVINA (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
Traditional dishes of Bosnia and Herzegovina represent a wealth of flavors and culture shaped over centuries by the historical and social influences of various conquerors. These dishes reflect a blend of Ottoman, Mediterranean, Austro-Hungarian and Balkan cuisines, where locally sourced ingredients have been transformed into diverse and recognizable dishes. Each region in Bosnia and Herzegovina boasts its specific culinary traditions. In eastern Herzegovina, cuisine is known for dishes like japrak and cicvara, while Prijedor and Banja Luka are famous for banjalučki ćevap and pita. Sarajevo offers iconic dishes such as sarajevski ćevap and begova čorba. The Krajina region is renowned for kljukuša and other varieties of pita, Zenica and Žepče areas preserve authentic recipes that combine simplicity with rich flavors. Materials for the study include books, journals, academic theses, video materials, websites and live communication (interviews and conversations). Descriptive and analytical methods were used to document and analyze culinary customs. The descriptive method explains traditional dishes’ ingredients, preparation methods, and cultural significance. The analytical method focused on comparing and contrasting these customs across different regions. The research revealed significant dish differences regarding preparation methods, names and habits across the country. Preserving these customs is essential for maintaining cultural identity and heritage. Efforts to document and promote these culinary traditions can help and maintain the cultural heritage of Bosnia and Herzegovina for future generations. The research has been conducted in the frame of the subject „Culture of eating in Bosnia and Herzegovina“. The aim was to collect and preserve traditional dishes of Bosnia and Herzegovina highlighting regional differences between Mediterranean-influenced Herzegovina and Central European-inspired northern and central Bosnia.